Complete mitogenome assemblies from a panel of 13 diverse potato taxa. Issue 3 (4th March 2021) - Achakkagari, Sai Reddy; Bozan, Ilayda; Anglin, Noelle L.; Ellis, David; Tai, Helen H.; Strömvik, Martina V.
Abstract: Mitochondrial DNA is maternally inherited and is shown to affect nuclear–cytoplasmic interactions in potato. Analyzing the mitogenome helps understand the evolutionary relationships and improve breeding programs in potato. We report complete mitogenome sequences from a panel of 13 potato accessions of various taxa. Each mitogenome has three independent circular molecules, except one of the S. bukasovii sample BUK2, which has a single circular molecule. Each mitogenome code for 37 non-redundant protein-coding genes, three rRNAs, 20 tRNAs, and 19 hypothetical open reading frames. Phylogenetic analysis reveals congruency between plastome and mitogenome phylogeny.